New methods for mobility performance measurement in wheelchair basketball - Van Der Slikke, R. M. A.; Berger, M. A. M.; Bregman, D. J. J.; Veeger, H. E. J. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Increased professionalism in wheelchair sports demand a more precise and quantitative measure of individual wheelchair mobility performance, to allow it to be an evaluation measure of wheelchair setting or training optimization. This research describes the application of an inertial sensor based method for measuring wheelchair kinematics and a factor analysis based selection of outcomes best describing wheelchair mobility performance. This set of kinematic outcomes was analysed for sensitivity towards wheelchair performance differences due to competition level and classification of the match data of 29 wheelchair basketball athletes. The method proved sensitive and is believed to provide a solid basis for a kinematics based definition of wheelchair mobility performance in sports.